Oriented intergrowth of the catalyst layer in membrane electrode assembly for alkaline water electrolysis - Lei Wan; Maobin Pang; Junfa Le; Ziang Xu; Hangyu Zhou; Qin Xu; Baoguo Wang (Nature Communications, 2022)
While membrane electrode assembly water electrolyzers are a promising renewable energy technology, further optimizations are needed before wide-spread implementation can occur. Here, authors examine a device with a porous membrane that enables oriented catalyst intergrowth to improve performances.